Analisis Hubungan Pola Konsumsi dan Aktivitas Fisik dengan Status Gizi Atlet Senior Woodball Damai United Kabupaten Kutai Kartanegara - Nisa, Dachniar Arsilla Khairatun; Wiryanto, Wiryanto; Ratnawati, Ratnawati (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2024)
This research aim of this research is to determine the relationship between consumption patterns and physical activity with the nutritional status of senior United Woodball damai athletes in Kutai Kartanegara Regency. The research method uses an quantitative approach with a cross sectional research desain. Have The sample, namely all senior woodball athletes at damai United, Kutai Kartanegara Regency, is known to be 21 people by taking total sampling data. The independent variables are consumption patterns and physical activity of athletes obtained by interviews using the SQ-FFQ form questionnaire and 24-hour physical activity recall interviews using the PAL formula. Data analysis using the chi-square test shows that there is a significant relationship between consumption patterns and athletes' nutritional status (p-value = 0.02) in contrast to the physical activity variable which does not have a significant relationship with athletes' nutritional status (p-value = 0 .31). Conclusion, research shows that there is a significant relationship between consumption patterns and athletes' nutritional status and the physical activity variable which does not have a significant relationship with nutritional status of senior United Woodball damai athletes in Kutai Kartanegara Regency. Keywords: Physical Activity, Athletes, Consumption Patterns, Nutritional Status.